Histologia e histoquímica da glândula androgênica dos caranguejos Ucides cordatus (Decapoda: Ocypodidae) e Goniopsis cruentata (Decapoda: Grapsidae), do estuário do Rio Ceará, Brasil - Leite, Marcos de Miranda Leão (2009)
The androgenic gland has been shown to control sexual differentiation in decapods by secreting a hormone capable of determining the primary, secondary and behavioral aspects of the male. The objective of this paper was to make a histological and histochemical description of the androgenic gland of two mangrove crab species, Ucides cordatus and Goniopsis cruentata, at the Ceará River estuary, Brazil, based on a forty-specimen sample of each species. Fragments of the vas deferens were preserved in Bouin’s solution for 24 hours and submitted to routine histological analyses. The androgenic gland of the two species was observed microscopically to lie along the vas deferens, beginning at the location where the latter penetrates the musculature of the endofragmal skeleton. The gland consists of a sinuous string of irregularly shaped cells overlying a thick, circular and striated muscle layer, not restricted to the subterminal region. The morphology of the androgenic gland of U. cordatus and G. cruentata is similar, matching the general descriptions published for other decapod species.